Nietzsche's Naturalist Deconstruction of Truth A World Fragmented in Late Nineteenth-Century Epistemology. - Bornedal, Peter (Lexington Books, 2019)
This book presents a new interpretation of Nietzsche's discussions of truth and knowledge, covering the period from his early essay "On Truth and Lies" to his late notebooks. It views these discussions in the context of the neo-Kantian, Naturalist, Positivist, and Pragmatic schools influential in Nietzsche's late nineteenth-century Europe.